Results for the Groups SL(2,34) and SL(2,36) - Mohammed IbrahemLfta, Niran Sabah Jasim (Mathematical Statistician and Engineering Applications, 2022)
The character table of rational representations and the induced characters table study to gain the Artin indicator for the groupsSL(2,34) and SL(2,36) in this work.